A structural analysis of heparin‒like glycosaminoglycans using MALDI‒TOF mass spectrometry. Issue 2 (2004) - Kett Kett, Warren C. Warren C.; Coombe Coombe, Deirdre R. Deirdre R.
Abstract : Mass spectrometry (MS) techniques have spear‒headed the field of proteomics. Recently, MS has been used to structurally analyse carbohydrates. The heparin/heparan sulfate‒like glycosaminoglycans (HLGAGs) present a special set of difficulties for structural analysis because they are highly sulfated and heterogeneous. We have used a matrix‒assisted laser desorption/ionization time of flight mass spectrometry (MALDI‒MS) technique in which heparin fragments are non‒covalently bound to basic peptides of a known mass, so as to limit in‒source desulfation and hence afford an accurate mass. We examined a range of different sized fragments with varying degrees of sulfation. The potential of combining the MALDI‒MS technique with enzymatic digestion to obtain saccharide sequence information on heparin fragments was explored. A disaccharide analysis greatly assists in determining a sequence from MALDI‒MS data. Enzymatic digestion followed by MALDI‒MS allows structural data on heparin fragments too large for direct MALDI‒MS to be obtained. We demonstrate that synthetic sulfated oligosaccharides can also be analysed by MALDI‒MS. There are advantages and limitations with this methodology, but until superior MS techniques become readily accessible to biomedical scientists the MALDI‒MS method provides a means to structurally analyse HLGAG fragments that have therapeutic potential because of their ability to bind to and functionally regulate a host of clinically important proteins.